Two Souls, One Body: The Ejagham Doctrine of Dual Spiritual Substance and Its Philosophical Implications - Gregory Ajima Onah; Godwin Michael Effiom; Gabriel Aduma Odey (Universitas Negeri Makassar, 2026)
This study examines the Ejagham (Ekoi) doctrine of dual spiritual substance, a distinctive philosophical anthropology originating among the indigenous communities of the Lower Cross River region of southeastern Nigeria and southwestern Cameroon. According to this doctrine, every human being possesses two souls: one that permanently inhabits the physical body and another that can be dispatched to animate an animal in the forest following the consumption of a family-transmitted magical potion. Drawing on ethnographic accounts, colonial records, and contemporary missiological research, this paper reconstructs the logical structure of the Ejagham dual-soul doctrine and evaluates its philosophical implications for several core areas of Western philosophy. These areas include the mind-body problem, personal identity over time, the nature of consciousness, and the relationship between human and non-human animals. The analysis demonstrates that the Ejagham doctrine challenges Cartesian substance dualism by proposing a form of pluralistic spiritual anthropology that resists reduction to Western categories. The doctrine also problematizes psychological continuity theories of personal identity by suggesting that a single person can simultaneously occupy two distinct biological bodies. Furthermore, the practice of dispatching the second soul to possess animals raises questions about the boundaries of consciousness and the moral status of non-human creatures. The study concludes that the Ejagham dual-soul doctrine represents a philosophically sophisticated indigenous theory worthy of serious engagement by contemporary philosophers of mind and metaphysicians